Do environmental policies affect global value chains? A new perspective on the pollution haven hypothesis - Koźluk, Tomasz (OECD Economics Department Working Papers, 2016)
Increasing international fragmentation of production has reinforced fears that industrial activity may flee to countries with laxer environmental policies - in line with the so-called Pollution Haven Hypothesis (PHH). If PHH effects are strong, domestic responses to environmental challenges may prove ineffective or meet strong resistance. Using a gravity model of bilateral trade in manufacturing industries for selected OECD and BRIICS countries over 1990s-2000s, this paper studies how exports are related to national environmental policies. Environmental policies are not found to be a major driver of international trade patterns, but have some significant effects on specialisation. More stringent domestic policies have no significant effect on overall trade in manufactured goods, but are linked to a comparative disadvantage in "dirty" industries, and a corresponding advantage in "cleaner" industries. The effects are stronger for the domestic component of exports than for gross exports, yet notably smaller than the effects of e.g. trade liberalisation